Systolic blood pressure variability is an important predictor of cardiovascular outcomes in elderly hypertensive patients - Chowdhury, E.; Owen, A.; Krum, H.; Wing, L.; Nelson, M.; Reid, Christopher (2014)
Obectives: In hypertensive persons aged 60 years or below, visit-to-visit SBP variability is directly associated with cardiovascular events, especially stroke. It is unclear whether such a relationship exists for older persons. We investigated whether there is a relationship between visit-to-visit SBP variability and cardiovascular events in an elderly population, and identified the factors associated with increased SBP variability. Methods: Information from 49771 visits of 5880 patients aged at least 65 years being treated for hypertension in the Second Australian National Blood Pressure study was used. Patients were followed for 4.1 (median) years and had eight (median) doctor visits during the study. SBP variability was defined as within-individual SD of SBP across study follow-up visits. Results: Increased visit-to-visit SBP variability was found to be a strong predictor for future cardiovascular events in this elderly population. The hazard ratio (95% confidence interval) for any first fatal/nonfatal cardiovascular event for highest decile compared with lowest decile of SBP variability was 2.18 (1.52-3.13) after adjusting for sex, age, treatment including other baseline variables, and average on-treatment SBP. A similar effect was observed for stroke (hazard ratio 2.78, 1.28-6.05), myocardial infarction (hazard ratio 4.11, 1.87-9.06), and heart failure (hazard ratio 4.79, 1.82-12.62). Highest SBP variability was also a predictor of post-trial fatal cardiovascular events. Increased visit-to-visit SBP variability was related to age, pulse pressure, changing physicians, smoking, treatment allocation, and the use of multiple BP-lowering drugs. Conclusion: These findings suggest that reducing visit-to-visit SBP variability might be an important objective in addition to conventional blood pressure-lowering in elderly hypertensive patients. © 2014 Wolters Kluwer Health | Lippincott Williams & Wilkins.